Piero di Cosimo : painter of faith and fable - Geronimus, Dennis, 1972-; Kwakkelstein, Michael W., 1963- (Brill, 2019)
2015 could rightly be called 'The Year of Piero di Cosimo'. Piero's (1462-1522) critical fortunes have been much revived and his admirers? sense of curiosity piqued by two exhibitions, organized by the National Gallery of Art, Washington, DC, and the Galleria degli Uffizi, Florence. Together, the exhibitions marked and celebrated a pair of firsts. The first-ever major retrospectives devoted entirely to Piero?s artistic career and the first joint-exhibition collaboration between the National Gallery of Art and the Uffizi in the distinguished history of the two institutions. It could be said that the study of Piero di Cosimo belongs no less to the history of imagination than to the history of art. As was true for Giorgio Vasari five centuries ago, Piero?s highly personal visual language remains a moving target for modern scholars. Yet, as surprising and alluringly strange as his pictorial solutions appear, it may be claimed that we have never known or understood as much about Piero as we do today. Freed from the powerful spell of Vasari?s biography-cum-cautionary tale, the Piero that emerges is not solely a conjurer of the uncanny, but a sensitive observer of the natural and manmade worlds, humans and beasts, surfaces and coloristic effects, phenomena material and ephemeral.
"The thirteen essays comprising the present volume spring from the proceedings of a two-day conference hosted by The Dutch University Institute for Art History, scheduled to coincide with the final days of the Uffizi Piero exhibition in late September 2015."
Keywords: Piero, -- di Cosimo, -- 1462-1521 -- Congresses.; Piero, -- di Cosimo, -- 1462-1521 -- Congrès.; Piero, -- di Cosimo, -- 1462-1521; ART -- History -- General.; Conference papers and proceedings